The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1073/pnas.0409904102
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of genes expressed in peripheral blood mononuclear cells predicts glucocorticoid sensitivity in asthma patients

Abstract: Gene expression profiles were examined in freshly isolated peripheral blood mononuclear cells (PBMC) from two independent cohorts (training and test sets) of glucocorticoid (GC)-sensitive (n ‫؍‬ 64) and GC-resistant (n ‫؍‬ 42) asthma patients in search of genes that accurately predict responders and nonresponders to inhaled corticosteroids. A total of 11,812 genes were examined with high-density oligonucleotide microarrays in both resting PBMC (106 patients) and cells treated in vitro with IL-1␤ and TNF-␣ comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 45 publications
2
105
0
3
Order By: Relevance
“…Complementary approaches may also be required to fully characterize the underlying architecture. For example, expression profiling in human tissues and animal models 51,52 can identify interacting sets of genes that could serve as candidates or provide quantitative phenotypes (eQTLs) 53 for genetic studies; bioinformatic 54 or systems-based approaches 55 can identify disease-related variants that interact in molecular or biochemical pathways; and functional analyses of associated variants or haplotypes can provide clues to pathogenesis. 43,56 Such 'molecular phenotyping' of patients with asthma or atopic diseases may inform decisions regarding treatment, and thereby laying the foundation for genomic medicine in the next decade.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Complementary approaches may also be required to fully characterize the underlying architecture. For example, expression profiling in human tissues and animal models 51,52 can identify interacting sets of genes that could serve as candidates or provide quantitative phenotypes (eQTLs) 53 for genetic studies; bioinformatic 54 or systems-based approaches 55 can identify disease-related variants that interact in molecular or biochemical pathways; and functional analyses of associated variants or haplotypes can provide clues to pathogenesis. 43,56 Such 'molecular phenotyping' of patients with asthma or atopic diseases may inform decisions regarding treatment, and thereby laying the foundation for genomic medicine in the next decade.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Therefore, current research in asthma has focused on the discovery of novel, more specific pathways that coordinate airway-obstructive disease in the setting of allergic inflammation and narrow-spectrum modulators of pathways critical to the disease phenotype. Widely used as part of these endeavors are proteomics-and genomics-based approaches, which have indeed identified novel inflammatory biomarkers in human and experimental asthma [5][6][7]. Bronchoalveolar lavage (BAL) fluid is perhaps the most widely used biological sample for the identification of novel asthma biomarkers through proteomics, although serum, whole lung and CD3 + T cells have also been used [8][9][10][11].…”
mentioning
confidence: 99%
“…These results are in keeping with results from an expression gene-array study profiling genes expressed in peripheral blood mononuclear cells from glucocorticoid-sensitive and -resistant asthma patients. 41 A second GWA study, using self-reported asthmadiary entries from child subjects, identified and replicated three SNPs (rs1558726, rs2388639, and rs10044254) that associated specifically with ICS-induced improvements in self-reported asthma scores in pediatric asthma patients. 42 The SNP rs10044254 lies within the FBXL7 gene, and is associated with decreased expression of the transcript.…”
Section: Gwa Studies Of Responses To Asthma Treatmentmentioning
confidence: 98%